2011
DOI: 10.1158/1078-0432.ccr-10-1694
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Efficacy of PKI-587, a Highly Potent Dual PI3K/mTOR Kinase Inhibitor

Abstract: Purpose: The aim of this study was to show preclinical efficacy and clinical development potential of PKI-587, a dual phosphoinositide 3-kinase (PI3K)/mTOR inhibitor.Experimental Design: In vitro class 1 PI3K enzyme and human tumor cell growth inhibition assays and in vivo five tumor xenograft models were used to show efficacy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
107
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 48 publications
15
107
1
Order By: Relevance
“…In preclinical models, inhibiting the PI3K pathway showed synergy with cytotoxic agents, enhancing its efficacy by potentiating apoptosis (41). In addition, dual inhibition of the RAF/MEK and PI3K/AKT/mTOR pathways seems to be required for complete abrogation of downstream effectors in RASmutant tumors (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical models, inhibiting the PI3K pathway showed synergy with cytotoxic agents, enhancing its efficacy by potentiating apoptosis (41). In addition, dual inhibition of the RAF/MEK and PI3K/AKT/mTOR pathways seems to be required for complete abrogation of downstream effectors in RASmutant tumors (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…GSK2126458 and PKI-587 are highly selective and potent small-molecule inhibitors which could effectively suppress both multiple class I PI3K isoforms and mTOR kinase activity (24,25). GSK2126458 has been identified as a highly potent, orally bioavailable inhibitor of p110a, p110b, p110g, p110d, mTORC1, and mTORC2.…”
Section: Introductionmentioning
confidence: 99%
“…PKI-587 is a highly potent dual inhibitor of PI3Ka, PI3Kg, and mTOR. Preclinical studies have demonstrated potent inhibitory effects of PKI-587 on a variety of human cancer cell lines, such as breast, glioma, lung, melanoma, colon, and liver cancer (25,26). Because PKI-587 has strong antitumor activity in vitro and in xenograft models, it is currently being evaluated in a phase I clinical trial in patients with solid tumors (NCT00940498).…”
Section: Introductionmentioning
confidence: 99%
“…This molecular knowledge has stimulated the development of news inhibitors termed dual PI3K-mTOR inhibitors that include NVP-BEZ235, XL765, BGT226, PI-103, PF-04691502, PKI-587 and GDC-0980 [142][143][144][145][146][147][148]. Comparing with the other types of PI3K pathway inhibitors, dual PI3KmTOR inhibitors have the possible advantage of inhibiting all PI3K catalytic isoforms, mTORC1 and mTORC2 [6].…”
Section: Dual Mtor/ Pi3k Inhibitorsmentioning
confidence: 99%
“…Comparing with the other types of PI3K pathway inhibitors, dual PI3KmTOR inhibitors have the possible advantage of inhibiting all PI3K catalytic isoforms, mTORC1 and mTORC2 [6]. The catalytic sites of PI3K and mTOR share a high degree of sequence homology, thus enabling the abrogation of the catalytic activity of both PI3K and mTOR, consequently blocking downstream signaling related to cell proliferation, survival, and angiogenesis [142][143][144][145]. Therefore, these inhibitors may effectively turn off this pathway completely and display best efficacy in feedback inhibition normally observed with mTORC1 inhibitors [149].…”
Section: Dual Mtor/ Pi3k Inhibitorsmentioning
confidence: 99%